Automatic Generation of Data Conversion-Programs Using a Data Description Language (DDL). Volume II. Appendix A. User Guide, Appendix B. SAPG User Guide, Appendix C. DDL Overlay, Appendix D. DDL Formats, Appendix E. Extended Backus Naur Form with Subroutine Calls (EBNF/WSC) for DDL. - Ramirez,Jesus Arturo (1973)
The Data Description (DDL) and the Data Manipulation Language (DML) have been developed to serve as a new type of 'utility' in computer systems. It is to be used to process data bases or data files, with existing formats and organizations, and produce these in new desired forms. The manual presents the specifications of both DDL and DML and examples of their use. In addition to examples which demonstrate the correct usage of each statement in DDL and DML, there is a set of comprehensive examples which illustrate some of the broad applications of DDL and DML. See also Volume 1, AD-761 160.